2018
DOI: 10.1111/dewb.12199
|View full text |Cite
|
Sign up to set email alerts
|

Consent for participating in clinical trials ‐ Is it really informed?

Abstract: The article explores the challenges of ensuring voluntary and informed consent which is obtained from potential research subjects in the north-eastern part of Romania. This study is one of the first empirical papers of this nature in Romania. The study used a quantitative survey design using the adapted Quality of Informed Consent (QuIC) questionnaire. The target population consisted of 100 adult persons who voluntarily enrolled in clinical trials. The informed consent form must contain details regarding the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Even so, most authors agree that there are more common characteristics than differences, and that the differences identified are not categorical. Most studies that analysed differences in the understanding of informed consent in clinical trials by gender found no differences [ 4 , 6 , 20 ]. Indeed, the few studies that identified differences mostly found a better understanding by women [ 21 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, most authors agree that there are more common characteristics than differences, and that the differences identified are not categorical. Most studies that analysed differences in the understanding of informed consent in clinical trials by gender found no differences [ 4 , 6 , 20 ]. Indeed, the few studies that identified differences mostly found a better understanding by women [ 21 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patient information and consent forms are increasingly long and difficult to understand. They are usually written in complex language (above the recommended grade 8 reading level) and often omit significant information [ 2 , 3 ].Several studies have reported a lack of understanding of some content [ 4 , 5 ], and no significant advances have been made in recent decades [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, according to the Alexa�Stratulat et al survey, despite the patients understanding of the general principles of conducting a clinical trial as described in the informed consent form, the researchers efforts should be focused on the patients to help them better understand con� sent, in particular the meaning of the trial and protection of their interests. 13 The factor that determined the participa� tion in a clinical trial to the greatest extent (36%) was the greater access to innovative therapy. A higher number of im� aging tests encouraged almost half of the respondents (48%) to participate in the trial.…”
Section: Discussionmentioning
confidence: 99%
“…In the hanging cases, death leading self-induced external and internal traumatic injuries were found at the cervical region, without other injuries with significance of an attack-defence action. The in-hospital suicide rate can be reduced by developing strategies to combat the phenomenon, with the application of educational measures for medical staff involved in patient care (Xue et al 2020;Alexa-Stratulat et al 2018).…”
Section: Discussionmentioning
confidence: 99%